Moderating Role of Resilience Between Depression and Stress Response of Vocational Middle School Students During the COVID-19 Pandemic - Jin, Mingqi; Ding, Lingling; Fan, Jiali; Sheng, Xin; Luo, Bingqing; Hang, Ronghua; Feng, Linpu; Huang, Long (Frontiers in Psychiatry, 2022)
Object In this study, we aimed to explore the influences of stress responses and psychological resilience on depression of vocational middle school students during the initial COVID-19 outbreak in China. Methods An online questionnaire survey on the students of a medical school in Jiangxi Province, China, and obtained 3,532 valid questionnaires. A self-compiled general situation questionnaire, Stress Response of COVID-19 Questionnaire, the Resilience Scale for Chinese Adolescents and Center for Epidemiological Studies Depression Scale (CES-D) were used. Hierarchical regression analysis was used to explore the regulatory role of psychological resilience between stress response and depression. Results (1) There were significant differences in gender between vocational middle school students' evaluation (t = 3.07, P = 0.002) and defense (t = 3.28, P = 0.001) of the pandemic. Males had higher cognitive evaluation of the pandemic than females, and females had more defense against the pandemic than males. (2) There is a significant difference between vocational middle school students from different grades in depression level (F = 3.62, P = 0.03), pneumonia defense (F = 13.65, P < 0.001) and pneumonia panic (F = 3.10, P = 0.045). (3) Depression level (F = 7.17, P < 0.001), pneumonia evaluation (F = 2.78, P = 0.04) and pneumonia panic (F = 3.32, P = 0.02) of the students concerning the spatial distance of the pandemic. (4) The severity of urban pandemic affects the evaluation of pneumonia among vocational middle school students. (5) Depression was negatively correlated with psychological resilience and pneumonia evaluation, and positively correlated with pneumonia panic. Psychological resilience was positively correlated with pneumonia evaluation and pneumonia defense, and negatively correlated with pneumonia panic. (6) Psychological resilience could reduce the level of depression caused by pneumonia evaluation and pneumonia panic. Conclusion There were significant differences in depression level and stress responses in grades, gender and spatial distance of pandemic. Resilience has a significant negative moderator effect on the relationship between pandemic panic and depression. Resilience has a significant positive moderator effect on the relationship between pandemic evaluation and depression.